SURVEI TENTANG MOTIVASI ORANG TUA MENGIKUTSERTAKAN ANAKNYA DI MATARAM SOCCER ACADEMY TAHUN 209 - Soemardiawan Soemardiawan; Ismail Marzuki (Lembaga Penelitian dan Pendidikan Mandala, 2019)
This research aims to know the motivation of parents to include their children in Mataram Soccer Academy., IN Mataram. This research was conducted in Mataram Soccer Academy.field, GOR Turida Mataram from December 2th to December 9nd 2019. This research used descriptive method by using survey technique in the form of questionnaire. The sampling technique was taken from 60 parent’s samples who involve their children in Mataram Soccer Academy City Mataram. The instruments used were questionnaires and Likert Scale for choice category. The testing of instrument validity used Product Moment for motivation variable. The reliability for variable motivation used Alpha Cronbach formula. The research result showed that the highest motivation of parents to involve their children to Mataram Soccer Academy city Mataram is motivated by the factor of appreciation needs by 29%. Therefore, the appreciation factor is the important thing for parents to involve their children to the academy.